2016
DOI: 10.1177/0218492316640953
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin level for prediction of postoperative infection in cardiac surgery

Abstract: The diagnostic accuracy of procalcitonin for bacterial infection is fairly high. Acute Physiology and Chronic Health Evaluation-II score is a better predictor of mortality and morbidity than absolute procalcitonin level. Procalcitonin > 7 ng mL(-1) can prognosticate and identify the high-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…found that PCT >7 ng/ml had 95% sensitivity and 80% specificity to identify bacterial infection after cardiac surgery. [30] The early postoperative increase in serum PCT in the absence of infection after cardiac surgery shows that PCT is influenced by the postoperative inflammatory process related to CPB. Therefore, this increase may interfere with the diagnosis of infection during the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…found that PCT >7 ng/ml had 95% sensitivity and 80% specificity to identify bacterial infection after cardiac surgery. [30] The early postoperative increase in serum PCT in the absence of infection after cardiac surgery shows that PCT is influenced by the postoperative inflammatory process related to CPB. Therefore, this increase may interfere with the diagnosis of infection during the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…PCT continues to be investigated in several observational and interventional studies. It has been demonstrated to have good performance characteristics for the identification of bacterial infection and sepsis [2,[17][18][19][20][21]. However, the evidence on PCT guided antibiotic therapy is less forthcoming.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In the ICU, PCT and potentially delta PCT 25 were found to be a predictor of bacterial infection in the surgical population. 26,27 PCT was also able to predict anastomotic leaks 28 and infection after colorectal surgery 29,30 as well as mesenteric ischemia after cardiac surgery. 31 Other small outpatient and ED studies showed the diagnostic utility of PCT in identifying infection in patients with rheumatoid arthritis, 32 and differentiating erysipelas from deep vein thrombosis.…”
Section: Evidence -Observational Studies Identificationmentioning
confidence: 96%